Readability test of RFID temperature sensor embedded in fresh concrete - Kang, Julian H.; Gandhi, Jasdeep (Journal of Civil Engineering and Management, 2010)
Concrete maturity technology is used to predict the strength of concrete being cured and make an informed decision for stripping the formworks. However, the current concrete maturity method uses temperature sensors that require an extensive wiring, which is not often acceptable on construction site due to harsh working environment. Radio Frequency Identification (RFID) technology provides a solution for the wiring issue because of its ability of sending data wirelessly. An RFID tag integrated with a temperature sensor and placed within fresh concrete may be able to read temperatures of concrete and transmit them to an RFID reader wirelessly in real‐time. It may then enable construction professionals to use concrete maturity technology to make an informed decision for stripping the formworks without having to worry about wiring issues on construction site. However, the previous research indicated that the RFID signal gets dispersed in liquid medium. One may speculate then how well RFID signals can travel through fresh concrete with high water content. Would water content of fresh concrete affect the readability of RFID tags? Would the tag's burying depth within fresh concrete affect its readability? This paper presents the results of our investigation on the readability of RFID tags placed in fresh concrete in the early stage of the curing process.First Published Online: 10 Feb 2011